Developmental pattern of fetal growth hormone, insulin-like growth factor I, growth hormone binding protein and insulin-like growth factor binding protein-3. Issue 2 (1st September 1997) - Pirazzoli, P; Cacciari, E; De Iasio, R; Pittalis, M C; Dallacasa, P; Zucchini, S; Gualandi, S; Salardi, S; David, C; Boschi, S
Abstract : AIMS: To evaluate the developmental pattern of fetal growth hormone (GH), insulin-like growth factor I (IGF-I), GH binding protein (GHBP) and IGF binding protein-3 (IGF-3); to determine the implications for fetal growth. METHODS: Serum GH, IGF-I, GHBP and IGFBP-3 were measured in 53 fetuses, 41 aged 20–26 weeks (group A) and 12 aged 31–38 weeks (group B). Fetal blood samples were obtained by direct puncture of the umbilical vein in utero. Fetal blood samples were taken to rule out β thalassaemia, chromosome alterations, mother to fetus transmissible infections, and for maternal rhesus factor. GHBP was determined by gel filtration chromatography of serum incubated overnight with 125 I-GH. GH, IGF-I and IGFBP-3 were determined by radioimmunoassay. RESULTS: Fetal serum GH concentrations in group A (median 29 μg/l, range 11–92) were significantly higher (P<0.01) than those of group B (median 16.7 μg/l, range 4.5–29). IGF-I in group A (median 20 μg/l, range 4.1–53.3) was significantly lower (P<0.01) than in group B (median 75.2 μg/l, range 27.8–122.3). Similarly, IGFBP-3 concentrations in group A (median 950 μg/l, range 580–1260) were significantly lower than those of group B (median 1920 μg/l, range 1070–1770). There was no significant difference between GHBP values in group A (median 8.6%, range 6.6–12.6) and group B (median 8.3%, range 6–14.3). Gestational age correlated positively with IGF-I concentrations (P<0.0001) and IGFBP-3 (P<0.0001) and negatively with GH (P<0.0001). GHBP values did not correlate with gestational age. Multiple regression analysis showed a negative correlation between GH:IGF-I ratio and fetal growth indices CONCLUSIONS: The simultaneous evaluation of fetal GH, IGF-I, IGFBP-3 and GHBP suggests that the GH-IGF-I axis might already be functional in utero . The progressive improvement in the efficiency of this axis in the last part of gestation does not seem to be due to an increase in GH receptors.